Dominant clade‐featured SARS‐CoV‐2 co‐occurring mutations reveal plausible epistasis: An in silico based hypothetical model. Issue 3 (1st November 2021) - Alam, A. S. M. Rubayet Ul; Islam, Ovinu Kibria; Hasan, Md. Shazid; Islam, Mir Raihanul; Mahmud, Shafi; Al‐Emran, Hassan M.; Jahid, Iqbal Kabir; Crandall, Keith A.; Hossain, M. Anwar
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has evolved into eight fundamental clades with four of these clades (G, GH, GR, and GV) globally prevalent in 2020. To explain plausible epistatic effects of the signature co‐occurring mutations of these circulating clades on viral replication and transmission fitness, we proposed a hypothetical model using in silico approach. Molecular docking and dynamics analyses showed the higher infectiousness of a spike mutant through more favorable binding of G614 with the elastase‐2. RdRp mutation p.P323L significantly increased genome‐wide mutations ( p  < 0.0001), allowing for more flexible RdRp (mutated)‐NSP8 interaction that may accelerate replication. Superior RNA stability and structural variation at NSP3:C241T might impact protein, RNA interactions, or both. Another silent 5′‐UTR:C241T mutation might affect translational efficiency and viral packaging. These four G‐clade‐featured co‐occurring mutations might increase viral replication. Sentinel GH‐clade ORF3a:p.Q57H variants constricted the ion‐channel through intertransmembrane–domain interaction of cysteine(C81)‐histidine(H57). The GR‐clade N:p.RG203‐204KR would stabilize RNA interaction by a more flexible and hypo‐phosphorylated SR‐rich region. GV‐clade viruses seemingly gained the evolutionary advantage of the confounding factors; nevertheless, N:p.A220V might modulate RNA binding with no phenotypic effect. Our hypothetical model needs further retrospective and prospective studies to understand detailed molecular events and their relationship to the fitness of SARS‐CoV‐2. Highlights: Most dominant spike mutation favors elastase‐2 binding. The polymerase mutant (P323L) virus may speed up replication that corresponds to higher mutations. ORF3a viroporin substitution (Q57H) decreases ion permeability. N protein mutation (RG203‐204KR) can increase nucleocapsid stability and help evade immunity. Co‐occurring mutations might modulate viral replication and transmission fitness through epistasis.